DDQ-Mediated Oxidation of Allylarenes: Expedient Access to Cinnamaldehyde-Containing Phenylpropanoids - Jiang, Tao-Shan; Zhang, Qingqing; Li, Guohui; Cheng, Xi; Cai, Yongping (Synthesis, 2018)
Phenylpropanoid natural products containing a cinnamaldehyde motif were easily synthesized from allylarenes mediated by 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) oxidation. Representative examples described herein are five types of 4-hydroxycinnamaldehyde derivatives from monolignols biosynthesis, Boropinal C, and 7-methoxywutaifuranal from plant extracts. Especially, simple synthesis of 7-methoxywutaifuranal was exploited through selective mono-oxidation and subsequent isomerization–ring-closing-metathesis strategy.
Keywords: phenylpropanoids; DDQ oxidation; 4-hydroxycinnamaldehydes; boropinal C; 7-methoxywutaifuranal